2021
DOI: 10.3390/joitmc7030170
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Model of Self-Efficacy and Organizational Citizenship Behavior Transmitted through Employee Engagement, Organizational Commitment and Job Satisfaction in the Thai Automobile Parts Manufacturing Industry

Abstract: This research aims to study the direct and indirect influence of self-efficacy on organizational citizenship behavior transmitted through employee engagement, organizational commitment and job satisfaction, and to examine employee engagement, organizational commitment and job satisfaction as partial or full mediators. The study samples were 400 employees in the automobile parts manufacturing industry. The study instruments used by previous researchers were applied and back translation was conducted on all ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 76 publications
3
29
0
3
Order By: Relevance
“…Although change-oriented organizational citizenship behavior is closely related to innovation-relevant behaviors at work, which are also critical for the innovation, it differs in that it is not included as a part of the organization’s formal reward system [ 81 ]. Behaviors beyond one’s formal job requirements are vital for innovation because followers who engage in change-oriented organizational citizenship behaviors are more willing to support their organizations’ success [ 82 ]. Thus, our findings shed light on the role of humor in energizing innovation in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Although change-oriented organizational citizenship behavior is closely related to innovation-relevant behaviors at work, which are also critical for the innovation, it differs in that it is not included as a part of the organization’s formal reward system [ 81 ]. Behaviors beyond one’s formal job requirements are vital for innovation because followers who engage in change-oriented organizational citizenship behaviors are more willing to support their organizations’ success [ 82 ]. Thus, our findings shed light on the role of humor in energizing innovation in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also found self-efficacy positively influenced OCB (Anfajaya & Rahayu, 2020;Pratiwi & Nawangsari, 2021), and those engaging in approach coping demonstrate higher levels of OCB (Lilly & Virick, 2013). Self-efficacy has a positive effect on employee engagement, organizational commitment, and job satisfaction, all of which can, in turn, positively influence OCB (Na-Nan et al, 2021).…”
Section: Discussionmentioning
confidence: 76%
“…For example, Faraz et al (2021) found that employees’ green self-efficacy when interacting with green servant leadership influenced pro-environmental behaviors. Na-Nan et al (2021) revealed that employees’ self-efficacy affected their engagement, job satisfaction and organizational commitment. Employees’ self-efficacy can also enhance their creativity performance (Ma et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%